2021
DOI: 10.1016/j.peptides.2021.170555
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin: Direct and indirect action on metabolism

Abstract: Highlights The roles of AVP on metabolism are described. A brief overview of the current knowledge concerning how AVP controls energy balance and feeding behavior is provided. We focused on physiological aspects including the relationship between AVP, circadian rhythmicity, and glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 199 publications
(235 reference statements)
1
32
0
Order By: Relevance
“…The V1bR agonist stimulated glucagon secretion at an early time point (10 minutes) but not at later postinjection times ( Figure 7A ), probably due to the limited metabolic stability of this peptide agonist (note that the parent compound arginine vasopressin, AVP, has a plasma half-life of only 15–20 minutes). However, the V1bR agonist had little or no effect on blood glucose and plasma insulin levels ( Supplemental Figure 8 , A and B), perhaps due to enhanced V1bR activity in other peripheral tissues ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The V1bR agonist stimulated glucagon secretion at an early time point (10 minutes) but not at later postinjection times ( Figure 7A ), probably due to the limited metabolic stability of this peptide agonist (note that the parent compound arginine vasopressin, AVP, has a plasma half-life of only 15–20 minutes). However, the V1bR agonist had little or no effect on blood glucose and plasma insulin levels ( Supplemental Figure 8 , A and B), perhaps due to enhanced V1bR activity in other peripheral tissues ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…The V1bR is part of a family of receptors that is activated by AVP, a nonapeptide synthesized by distinct neuronal subpopulations of the hypothalamus ( 49 ). Other members of this family are the V1a and V2 receptor subtypes ( 34 ). Under physiological conditions, an increase in plasma osmolality represents the major trigger of AVP release, leading to antidiuresis via activation of V2 receptors expressed by kidney collecting duct cells ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Six3 kiss males had comparable body weight to control ( Six3 flfl ) males from 3 to 12 weeks of age ( Figure 6 I), indicating the significant change in body weight developing after 4 weeks of age in Six3 syn males is unlikely to be driven by Six3 in kisspeptin neurons. We therefore shifted our focus to AVP and SS expressing neurons of the PVN and PeVN which are known to regulate metabolic status and the growth axis [ 52 , 53 ]. Using immunohistochemistry, we found that Six3 syn males and Six3 fl/fl controls had a comparable number of SS-expressing neurons in the PVN ( Figure 6 J, M), but Six3 syn males had a greater number of SS-expressing neurons in the PeVN compared to control mice ( Figure 6 K, N).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to oxytocin, AVP also affects a broad spectrum of metabolic parameters [ 173 ]. For example, acute endogenous activation of PVN AVP neurons decreases food intake, and peripheral administration of AVP further decreases brown adipose tissue thermogenesis in healthy rodent models [ 174 , 175 , 176 ].…”
Section: Sensory Cvos and Hypothalamic Circuits In Metabolic Regulationmentioning
confidence: 99%